Strength-ductility enhancement in high-Mn TWIP steel welded joints via optimized gas tungsten arc welding - Xingfu Wang; Nanle Yang; Juhua Liang; Jianguo Ma; Runxia Li; Biao Wang (Journal of Materials Research and Technology)
Medium-thick welded joints in high-Mn twinning-induced plasticity (TWIP) steel plate were fabricated using the multi-pass gas tungsten arc welding (GTAW) process, with the filler metal derived from the base material (BM) through hot rolling and drawing. The impact of GTAW process optimization on microstructural evolution and mechanical properties within the welded joints was evaluated. The welds primarily consist of a single austenitic phase with typical solidification structures, including cellular, columnar, and dendritic grains. By finely tuning the heat input parameters, a crack-free TWIP steel plate joint was successfully fabricated, with minimal detrimental precipitates present. Under welding conditions of a 120A current and a 30° V-groove angle, a notable enhancement in the strength-ductility trade-off of the welded joint (designated as the 120A-30° joint) was observed, with fracture initiating in the BM region. The 120A-30° joint exhibited an exceptional strength efficiency of 101 % and a significant improvement in impact toughness compared to that of the BM. Moreover, a quantitative analysis of strength contributions from the BM, heat-affected zone (HAZ), and fusion zone (FZ) was conducted and the result revealed a yield strength hierarchy: HAZ > FZ ≈ BM ≈ measured value. This observation can be attributed to the increased dislocation density and enhanced work-hardening capacity within the defect-free HAZ and FZ under optimal heat input conditions.